Cardiac arrest in a child during a combined general epidural anesthesia procedure - Soenarjo Soenarjo; Yudhi Prabakti; Edwin MP Siahaan; A Soemantri; M Sidhartani (Indonesian Pediatric Society Publishing House, 2016)
An increased risk of perioperative cardiac arrest in children, in comparison to adults, has been recognized. A number of factors associated with perioperative cardiac arrest have been identified, including young age, comorbidities, and emergency surgery. Since anesthesia-related cardiac arrest is uncommon, a multi-related database is required to understand the mechanisms of cardiac arrest and to develop preventive strategies. Most cardiac arrests occur during induction (37%) or maintenance (45%) of anesthesia, usually following one or more of the following antecedent events, i.e., bradycardia (54%), hypotension (49%), abnormality of oxygen saturation as measured by pulse oximetry (48%), inability to measure blood pressure (25%), abnormality of end- tidal CO 2 (21%), cyanosis (21%), or arrhythmia (18%). In 11% of cases, cardiac arrest occurred without recognized warning. There are only few reports in the literature, and in Kariadi Hospital, none has ever been reported. The aim of this report is to identify and discuss possible causes of cardiac arrest and to anticipate its complications.